1990
DOI: 10.1093/clinchem/36.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of type I collagen that mainly detects degradation products in serum: application to patients with liver diseases

Abstract: This radioimmunoassay for type I collagen mainly detects degradation products of the molecule in human serum samples. Type I collagen antigenicity in serum can be separated into two peaks by gel-filtration chromatography. The larger form represents collagen molecules (as shown by immunoblotting experiments), and (or) type I collagen with aminoterminal propeptide or intact procollagen molecules. The smaller form, the exact nature of which is not known, is quantitatively the principal antigenic form and is deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although, this hypothesis cannot be excluded, it seems unlikely, since other collagen‐related markers cleared by the kidney are also increased in PBC. Previous studies have found that PICP levels are elevated in patients with liver disease (23,24) …”
Section: Discussionmentioning
confidence: 98%
“…Although, this hypothesis cannot be excluded, it seems unlikely, since other collagen‐related markers cleared by the kidney are also increased in PBC. Previous studies have found that PICP levels are elevated in patients with liver disease (23,24) …”
Section: Discussionmentioning
confidence: 98%
“…Two radioimmunoassays, developed in the laboratory, were used for type I (CI) and type III (CIII) collagens. The CI assay detected mostly degradation products of type I collagen [20], whereas the CIII assay accounted for type III collagen synthesis [21]. The upper values for the CI and CIII assays were respectively 200 and 40 mg L ¹1 in healthy adults.…”
Section: Serum and Urinary Metabolites Of Extracellular Matrixmentioning
confidence: 99%
“…It also seems to detect increased osteolysis in myeloma and in bone metastases. A third radioimmunoassay for the main triple-helical region of Type I collagen molecule detects antigens of small molecular size, obvious breakdown products, in human serum [8]. Their concentration increases in liver cirrhosis; they have not been studied in bone disease.…”
mentioning
confidence: 99%